The DISCLOSURE FRAMEWORK OF RELATED PARTY TRANSACTIONS IN SELECTED ASEAN MEMBER STATES (UUM Journal of Legal Studies, 2020)
Related party transaction or RPT is a transaction that could either be harmful or beneficial to the company and minority shareholders. RPT can be considered as an efficient tool for the company or abused by the controlling shareholders. Therefore, one of the key factors to address this transaction is through disclosure. This study applied a content analysis method using materials that were largely library-based including primary and secondary data. The former was gathered from relevant theories to explain the application of the legal theories. Meanwhile, the latter was derived from published materials, such as textbooks, journal articles and online databases. In order to assess these materials, a combination of descriptive, critical and comparative data analysis approaches was employed in this study. This paper aims to understand the underlying applicable legal theories on RPT by analysing and comparing the disclosure framework in Malaysia, Singapore and Thailand that adopt the ASEAN Disclosure Standards (â€œADSâ€). This paper finds that there is a disparity in the disclosure standard among these states despite having ADS in place. This problem calls for a clearer ex-ante approval process in ADS and to consider the model from the European Unionâ€™s Shareholders Amending Directive 2017/828 to improve the disclosure framework in each jurisdiction. In conclusion, ADS indicated the requisite for the conflicted parties to declare and obtain approval from the minority shareholders however with unclear procedure and minimal threshold.